Taxonomic distinctness poorly reflects floristic quality in a wetland study system - Suneeti K. Jog (Elsevier, 2021)
Biomonitoring typically uses taxonomic diversity information while ignoring phylogenetic diversity. Evolutionary relatedness may offer deeper insight to how local assemblages relate with human disturbance and ecological degradation. Degradation of floristic quality may filter species with similar evolutionary traits, whereas intact floristic quality may limit phylogenetic clumping and increase representation of more distantly related taxa. We tested this hypothesis using average taxonomic distinctness (AvTD) and measures of floristic quality (mean ecological conservatism, native species richness, percent exotic species) in vascular plant assemblages of 115 wetlands in the US southern plains. In line with the hypothesis, we observed positive correlations with conservatism (r = 0.28, P = 0.0007) and native richness (r = 0.24, P = 0.0018) and a negative correlation (r = −0.21, P = 0.0169) with exotics, but the plotted relationships looked obscure. A strongly skewed AvTD distribution revealed a clear gradient in lower than expected AvTD. Responses along this gradient covaried with native richness (quadratic model R2 = 0.75) but showed no pattern with conservatism and a weak response to exotics. These results suggest that native richness has potential to predict lower than expected AvTD values. However, attributing these values to degraded floristic quality requires caution when richness is driven by sampling effects such as species-area relationships or has a non-linear relationship to human disturbance. Given the vague correlations and ambiguity of richness, plant taxonomic distinctness may not provide a clear bioindicator for wetlands. More work is needed to elucidate how evolutionary structure may play into bioassessment, which traditionally has been phylogenetically neutral.